Christopher: the holy giant - dePaola, Tomie (New York : Holiday House, 1994)
As Reprobus carries a child across a river one stormy night, the boy gets heavier and heavier until Reprobus feels he is carrying the world in his shoulders-thus goes the legend of the name Christ-bearer, or Christopher.
Keywords: Christopher, Saint-Juvenile literature; Christopher, Saint; Saints